2022
DOI: 10.3390/healthcare10101956
|View full text |Cite
|
Sign up to set email alerts
|

Dysarthria Speech Detection Using Convolutional Neural Networks with Gated Recurrent Unit

Abstract: In recent years, due to the rise in the population and aging, the prevalence of neurological diseases is also increasing year by year. Among these patients with Parkinson’s disease, stroke, cerebral palsy, and other neurological symptoms, dysarthria often appears. If these dysarthria patients are not quickly detected and treated, it is easy to cause difficulties in disease course management. When the symptoms worsen, they can also affect the patient’s psychology and physiology. Most of the past studies on dysa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Furthermore, Kashyap, et al showed that models trained on the "ta-ta-ta" and "British Constitution" tasks were able to capture disease progression over a two-year period [37]. Though some works reported high accuracy using CNN-based and gated recurrent unit-based deep learning models applied to mel spectrograms [48], [49], such results are likely optimistic as they were achieved using methodologies that did not ensure participant independence between training and testing sets [50]. A recent work by Song, et al, however, provides a comparable benchmark for the proposed models' performance [38].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Kashyap, et al showed that models trained on the "ta-ta-ta" and "British Constitution" tasks were able to capture disease progression over a two-year period [37]. Though some works reported high accuracy using CNN-based and gated recurrent unit-based deep learning models applied to mel spectrograms [48], [49], such results are likely optimistic as they were achieved using methodologies that did not ensure participant independence between training and testing sets [50]. A recent work by Song, et al, however, provides a comparable benchmark for the proposed models' performance [38].…”
Section: Discussionmentioning
confidence: 99%
“…Other models, including ADD and ADSLA, are classic machine learning methods, like RF and SVM, that are employed for classification problems [22]. When processing voice data, CNNs and GRUs each handle different tasks: CNNs record local patterns, GRUs represent sequential dependencies [39], and cascade convolution models frequently combine multiple convolutional layers.…”
Section: Comparative Analysismentioning
confidence: 99%
“…Since the recursive process in Step 1 is repeated, the amount of calculation is large. A gated-graph sequential neural network (GGS-NN) replaces the recursion process in Step 1 with a Gated Recurrent Unit (GRU), which is the gating mechanism in a recurrent neural network (RNN) and which has better performance on certain smaller datasets and removes the constraints of contraction mapping [86][87][88][89][90][91][92]. The GRU concept can be expressed using the following formula:…”
Section: Current Qsarmentioning
confidence: 99%